(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A The aim of this paper is to analyzed the characteristics of the Abbasid palaces (Qasr Al-Jawsaq Al-Khakani palace, Balaklora Palace and Al-Jaafari Palace) and applied the principles of architectural design on the plan of Abbasid palaces and made their comparative analysis. The research identified the principles of architectural design with six points, including proportionality, symmetry, balance, axes, repetition and gradation, beginning with a simplified definition of each palace and then each design principle and applying the principle to the plan of Abbasid palaces.